(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aims to calculate the financial returns of private education, and how far it can contribute to support the federal general budget, particularly the government education spending, via using statistical methods of the general trend equation. This equation is actually based on the use of one or more of the following methods in achieving a future forecast of the financial returns of private education. The moving squares and the least squares method have been used to do the purpose mentioned above the research concludes with many findings, the most important is that private education has great financial returns that may contribute to supporting the general budget by reducing the expenditure of government educational.